INOVASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI ERA INFORMATION AND COMMUNICATION TECHNOLOGY - Ummul Jazilah (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2021)
Digital era is a condition where everyone is able to access various informations on the network (online). It is available in cyberspace and make easier to access everything without space and time limitation. There is no world block after the invention of this system. The digital natives, has a tendency to search information through internet. They prefer to get advantage of smartphone features or other technological devices for entertainment or to fulfill primary needs. Music and movies can be enjoyed or downloaded freely or paid cheaply. For scientific needs and accessing information, one can get articles freely without any requirements in this digital era. This phenonema on the other hand is an encouraging thing that indicates a change of the world in a more advanced. This era has demanded learning innovation, and technological advances must be utilized as best as possible by educators, especially Islamic religious educators. Utilization of technology in the learning process is a must so that the learning process is not stagnant and rigid. Utilization or innovation of Islamic religious education learning must be carried out immediately, especially in the learning method. The internet as a learning media can be an alternative method of learning Islamic religious education. This can be in the form of e-learning, or applications which facilitate the learning material delivery, resulted learning process is more interesting.